2023
DOI: 10.9734/indj/2023/v19i3374
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity and Anxiolytic Activity Screening of Hydroalcoholic Leaf Extracts of Bryophyllum pinnatum, Terminalia catappa and Tapinanthus dodoneifolius Growing on Terminalia catappa Tree in MIce

Abstract: Aims: Hydroalcoholic T. dodoneifolius, B.pinnatum and T. catappa leaf extracts were investigated for their acute toxicity and anxiolytic activities. Study Design: Acute toxicity (LD50) was determined using the limit dose acute and Anxiolytic activities were assessed by open-field field behavioural testing in mice. Place and Duration of Study: The study took place in the Neurobehavioural room of Department of Pharmacology & Therapeutics, Faculty of Pharmacy, Ahmadu Bello University, Zaria in late December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…These findings may the first indicating that MPS extracts may not have cns depressant effect even though several studies have shown its extracts to possess anxiolytic activity [61,62]. This study may be the second report on extracts of Tapinanthus globiferus (TG) not exhibiting negative locomotory effect [13] in mice despite their reported anxiolytic activity [9,10]. The fact that extracts of these medicinal plants have been reported to exert significant anxiolytic activity with no significant sedative effect that may impact locomotion may suggest that the anxiolytic pharmacophores in these plants may be acting on a neural pathway quite distinct from the benzodiazepine GABAergic mechanism(s).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…These findings may the first indicating that MPS extracts may not have cns depressant effect even though several studies have shown its extracts to possess anxiolytic activity [61,62]. This study may be the second report on extracts of Tapinanthus globiferus (TG) not exhibiting negative locomotory effect [13] in mice despite their reported anxiolytic activity [9,10]. The fact that extracts of these medicinal plants have been reported to exert significant anxiolytic activity with no significant sedative effect that may impact locomotion may suggest that the anxiolytic pharmacophores in these plants may be acting on a neural pathway quite distinct from the benzodiazepine GABAergic mechanism(s).…”
Section: Discussionmentioning
confidence: 64%
“…Previously, crude aqueous methanol and fractionated leaf extracts of Tapinanthus globiferus on Azadirachta indica host tree have demonstrated anxiolytic activity comparable to that of diazepam [9][10]. Although the benzodiazepines, the prototype of which is diazepam, are regarded as gold standard in anxiolytic efficacy, their clinical usefulness is limited by such neurobehavioural adverse effects comprising cognitive, locomotor, sedative, hypnotic and abuse liabilities [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation